Does an mHealth system reduce health service use for asthma?. Issue 3 (14th September 2020) - To, Teresa; Lougheed, M. Diane; McGihon, Rachel; Zhu, Jingqin; Gupta, Samir; Licskai, Christopher
Background: Breathe is a mobile health (mHealth) application developed for the self-management of asthma in adults. There is evidence to suggest that mHealth interventions can be used for asthma control; however, their effects on the use of health services remain poorly understood. We sought to determine whether Breathe reduces health services use amongst asthma patients who used the app compared to controls who did not. Methods: The impact of Breathe on health services use was estimated using a quasi-experimental approach. Two groups of subjects who had participated in a previous randomised clinical trial were included: an intervention group of asthma patients who used the app for 12 months, and a group of controls who did not use the app but received equivalent quality asthma care. A third, external control group of asthma patients were matched to the intervention participants. Generalised linear mixed models were used to determine relative changes in rates of asthma hospitalisations, emergency department (ED) visits, outpatient physician visits and completion of pulmonary function tests (PFTs) over time. Results: A total of 677 individuals with asthma were included in the study: 132 in the intervention group, and 149 and 396 in the internal and external control groups, respectively. There were no statistically significant differences in the change of asthma hospitalisations, ED visits, physician office visits or completion of PFTs between the intervention group and either control group. Conclusions: Use of the Breathe app is not associated with changes in health services use in adults with asthma. Use of a mobile health application designed for asthma self-management was not associated with changes in asthma health services use or completion of pulmonary function testing in adults with asthma who use the application compared to those who did not https://bit.ly/2YojkeE